Effect of Linseed Oil Feeding on Serum Lipids and Fatty Acid Profile of Breast and Thigh Muscle in Broiler Chicken - Shunthwal, Jyoti; A.S. Yadav, A.S. Yadav; Sihag, Sajjan; Kumar, Rakesh; Baloda, Saurabh; ., Promila; Sheoran, Nancy (Indian Journal of Animal Nutrition, 2018)
Three hundred, day-old, commercial broiler chicks were randomly distributed into 5 treatment groups with 6 replicates of 10 chicks in each replicate for a period of 6 weeks. The birds in control group (T1) were offered maize and soybean meal based diet having sunflower oil @ 4% and 5% in starter and finisher diet, respectively. While in treatments T2, T3, T4 and T5 sunflower oil of basal diet was replaced with linseed oil @ 25, 50, 75 and 100%, respectively. The contents of palmitic acid and stearic acids in thigh muscle decreased (P<0.05) in treatment T4 and T5 as compared to control while SFA concentration of breast muscle decreased (P<0.05) in treatments having different levels of linseed oil. The linoleic acid and arachidonic acid content in both breast and thigh muscles decreased in treatments T3, T4 and T5 than the control group. The n-3 PUFA linolenic acid content increased (P<0.05) in treatments T2, T3, T4 and T5 as compared to control group. A significant increase (P<0.05) in n-3 PUFA and a decrease in n-6: n-3 ratio was noticed in breast and thigh muscle due to incorporation of linseed oil in the diets, the effect being more pronounced in treatment T5. Serum triglycerides level and cholesterol level was lower (P<0.05) in treatment T5 than control. There was no significant difference in serum HDL among the treatments while LDL level decreased (P<0.05) in T2, T3, T4 and T5 groups compared to control group. Thus, the inclusion of linseed oil in place of sunflower in broiler chcken diets enhanced beneficial long-chain n-3 PUFA and decreased ratio of n-6: n-3 FA in chicken breast and thigh muscle which could be advantageous for obtaining healthy chicken products.